Kajian Rancangan Dan Permasalahan Instalasi Pengujian Pompa Dan Turbin Model PLMTH Di STT-PLN - Eko Sulistyo; Gita Puspa Artiani; Teguh Febriyanto (Sekolah Tinggi Teknik - PLN, 2013)
In testing the water turbine installation should be able to test various types of water turbines and their characteristics. Known models such as the type of turbine, turbine pelton, francis, propeller / kaplan, and cross flow. pelton turbine is a turbine that has the characteristics of high head and a small discharge, whereas francis turbine for medium and discharge head being, as well as a turbine propeller / kaplan for low head dann large discharge. The test installation shall be able to accommodate the needs of characteristics (needs) of each turbine. Besides the problems of installation testing is also required measuring tools to measure / determine the magnitude of the parameter-parmeter time of testing, such as the flow of water entering the turbine, a large head of the turbine, the greater the power of the turbine, and the amount of rotation of the turbine when pengujian.Semua case must be thought out and designed to meet the requirements and testing purposes so that the results meet the desired accuracy.